Response of rice (Oryza sativa) to zinc sulphate incubated and blended with organic materials in sodic soil - KUMAR, D; CHAUHAN, R P; SINGH, B B; SINGH, V PAL (The Indian Journal of Agricultural Sciences, 2013)
In a field experiment on rice (Olyza sativa L.) in sodic soil, ZnS04 @ 20 and 30 kg/ha incubated and blended separately with pressmud and farmyard manure (each at 0.25 tonne/ha) was compared with the recommended dose of 40 kg/ha alone. Zinc sulphate at 20 kg/ha incubated or blended either with pressmud or farmyard mannre was at par with ZnSO4 at 40 kg/ha alone in respect of grain and straw yields of rice and N and Zn contents and their uptake by the crop. Incubation or blending of ZnS04 at 20 kg/ha with either of the organic materials also maintained almost equal amounts of available Zn in soil and recorded high recovery of applied Zn compared with ZnS04 at 40 kg/ha alone. Furiher, high available P in soil and hence in plants caused significantly more uptake of P with ZnS04 at 20 kg/ha incubated or blended with either of the organic materials than ZnS04 at 40 kg/ha alone. Thus, by incubation or blending of ZnSO4 at 20 kg/ha prior to its incorporation into the soil under rice, 50 % of the recommended dose of ZnS04 may be saved.